Access to work for disabled persons in South Africa: A rights critique - Meryl Candice du Plessis (Pretoria University Law Press (PULP), 2017)
Assumptions of inability and the perceived costs of employing disabled persons are two of the primary reasons why it has been impossible or difficult for many capable disabled persons to access work and to continue working. This book considers the South African legal framework that seeks to promote such access and critiques it with particular reference to the intersections of the rights to equality and access to social security. One of the primary arguments is the need for a more active conception of social security in which access to work for disabled persons is recognised as an integral component of promoting both social security and substantive equality.